A phase I study of talazoparib (BMN 673) combined with carboplatin and paclitaxel in patients with advanced solid tumors (NCI9782). (8th April 2022) - Leal, Ticiana A.; Sharifi, Marina N.; Chan, Nancy; Wesolowski, Robert; Turk, Anita A.; Bruce, Justine Y.; O'Regan, Ruth M.; Eickhoff, Jens; Barroilhet, Lisa M.; Malhotra, Jyoti; Mehnert, Janice; Girda, Eugenia; et al.
Abstract: Background: Inhibitors of poly(ADP‐ribose) polymerase (PARP) proteins potentiate antitumor activity of platinum chemotherapy. This study sought to determine the safety and tolerability of PARP inhibitor talazoparib with carboplatin and paclitaxel. Methods: We conducted a phase I study of talazoparib with carboplatin AUC5‐6 and paclitaxel 80 mg/m 2  days 1, 8, 15 of 21‐day cycles in patients with advanced solid tumors. Patients enrolled using a 3 + 3 design in two cohorts with talazoparib for 7 (schedule A) or 3 days (schedule B). After induction with 4–6 cycles of triplet therapy, patients received one of three maintenance options: (a) continuation of triplet (b) carboplatin/talazoparib, or (c) talazoparib monotherapy. Results: Forty‐three patients were treated. The MTD for both schedules was talazoparib 250mcg daily. The main toxicity was myelosuppression including grade 3/4 hematologic treatment‐related adverse events (TRAEs). Dose modification occurred in 87% and 100% of patients for schedules A and B, respectively. Discontinuation due to TRAEs was 13% in schedule A and 10% in B. Ten out of 22 evaluable patients in schedule A and 5/16 patients in schedule B had a complete or partial response. Twelve out of 43 patients received ≥6 cycles of talazoparib after induction, with a 13‐month median duration of maintenance. Conclusion: We have established the recommended phase II dose of Talazoparib at 250mcg on a 3‐ or 7‐day schedule with carboplatin AUC6 and paclitaxel 80 mg/m 2 on days 1, 8, 15 of 21‐day cycles. This regimen is associated with significant myelosuppression, and in addition to maximizing supportive care, modification of the chemotherapy component would be a consideration for further development of this combination with the schedules investigated in this study. Abstract : Carboplatin, paclitaxel and talazoparib followed by talazoparib maintenance is feasible with appropriate supportive care, and warrants further investigation across solid tumor types, particularly those with DNA repair pathway alterations, and supports further development of PARP inhibitor maintenance strategies in the advanced disease setting.